GUIDANCE AND COUNSELING TEACHER TENURE OF APPLICATIONS INSTRUMENTATION AT SMP OF METRO CITY - Sundari, Siti; Wibowo, Satrio Budi (Universitas Muhammadiyah Metro, 2014)
Abstract: Activity instrumentation applications is supporting activities that strongly supports the achievement of the effectiveness of counseling services organized by BK teacher. Goals to be achieved by the researchers is to determine how the level of mastery of instrumentation applications teacher guidance and counseling junior at Metro City. The quantitative Descriptive research design used. The results showed mastery of instrumentation applications BK junior high school teacher in the city of Metro is quite good, with the percentage of 64.81% . In all four aspects studied lowest percentages are aspects of the execution and reporting that is 15.46%, and which has the highest percentage is the aspect of evaluation ie 17.13%. Suggestions put forward, namely upgrading of instrumentation in guidance and counseling teacher training and seminars on instrumentation activities.Keyword: Instrumentation Applications, Master of Guidance and Counseling